Service Satisfaction Analysis With Servequal Method - Sumartini, Lilis Cucu (Universitas Ibn Khladun Bogor, 2023)
Service quality is a dynamic state that encompasses people, processes, goods, services, and the environment that either meet or beyond expectations. By contrasting customers' opinions of the services they really receive or obtain with what they genuinely expect or want in relation to a company's service qualities, one can determine the quality of the services provided. Finding out the outcomes of service measuring and satisfaction using the servequal method is the aim of the study. In contrast, the research approach makes use of quantitative techniques and the servequal method for measures. Based on the perceived quality of customers, this servqual service quality model carries out research. By calculating the gap between what customers expect and what they actually receive, the Servqual approach determines service quality. The findings indicated that a GAP value of 1 for tangible, reliability, responsiveness, certainty, and sympathy—a sign that the public's needs have not been satisfied—was the root reason of the public's discontent with the service. Conclusion: The community is generally dissatisfied with the services that employees deliver, according to calculations made on the dimensions of tangible, realibilty, responsiveness, certainty, and empathy. Nonetheless, the community expresses satisfaction with staff services in the empathy component of the fourth and fifth qualities.